Grating-based X-ray phase-contrast tomography of atherosclerotic plaque at high photon energies - Hetterich, Holger; Fill, Sandra; Herzen, Julia; Willner, Marian; Zanette, Irene; Weitkamp, Timm; Rack, Alexander; Schueller, Ulrich; Sadeghi, Mojtaba; Brandi, Richard; Adam-Neumair, Silvia; Reiser, Maximilian; et al. (Zeitschrift für Medizinische Physik, 2013)
Background: Tissue characterization of atherosclerosis by absorption-based imaging methods is limited due to low soft-tissue contrast. Grating-based phase-contrast computed tomography (PC-CT) may become an alternative for plaque assessment if the phase signal can be retrieved at clinically applicable photon energies. The aims of this feasibility study were (i) to characterize arterial vessels at low and high photon energies, (ii) to extract qualitative features and (iii) quantitative phase-contrast Hounsfield units (HU-phase) of plaque components at 53 keV using histopathology as gold standard. Materials and methods: Five human carotid artery specimens underwent grating-based PC-CT using synchrotron radiation of either 23 keV or 53 keV and histological work-up. Specimens without advanced atherosclerosis were used to extract signal criteria of vessel layers. Diseased specimens were screened for important plaque components including fibrous tissue (FT), lipid (LIP), necrotic core (NEC), intraplaque hemorrhage (IPH), inflammatory cell infiltration (INF) and calcifications (CA). Qualitative features as well as quantitative HU-phase were analyzed. Results: Thirty-three regions in 6 corresponding PC-CT scans and histology sections were identified. Healthy samples had the same signal characteristics at 23 keV and 53 keV with bright tunica intima and adventitia and dark media. Plaque components showed differences in signal intensity and texture at 53 keV. Quantitative analysis demonstrated the highest HU-phase of soft plaque in dense FT. Less organized LIP, NEC and INF were associated with lower HU-phase values. The highest HU-phase were measured in CA. Conclusion: PC-CT of atherosclerosis is feasible at high, clinically relevant photon energies and provides detailed information about plaque structure including features of high risk vulnerable plaques. © 2013.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Grating-interferometry; Synchrotron radiation; X-ray-based phase-contrast computed tomography